Corner of Botanical Building and Palace of Foods and Beverages (Western Publishing & Novelty Company)
Botanical Building and the Lagoon in front of it constitute a perennial beauty spot. Exotic lianas, orchids, gigantic bamboo and dainty palms delight the eye of the visitor in the building.